Zakat Fundraising Unit - Mosque Collaboration as Zakat Fund Manager: Strategy for Increasing Zakat Fund Collection - Syamsuri, Syamsuri; Adillah, Erika Rishan (Jurnal Internasional Ekonomi Islam, 2024)
Introduction: The phenomenon that occurs is that people still prefer to pay zakat to mosques due to the tradition passed down from generation to generation and easy access, especially for rural communities far from urban areas, as well as the strategic location of mosques in each area. So, it is necessary to maximize strength by establishing good relations with village officials, Islamic boarding schools, and especially mosques. Objectives: This research aims to create a collaborative concept for the excellence of the Zakat Management Unit with the characteristics of mosques to increase the collection of Zakat funds. Method: This research uses descriptive-qualitative methods with a literature review method. Data collection techniques involve selecting relevant sources and then classifying, categorizing, and interpreting the data. Results: The research results show the need for strategic steps to be taken by BAZNAS to collaborate with mosques. Then it ends with reporting, which is divided into two types. Firstly, reporting to the main mosque by accounting standard No. 109, which is forwarded to the regional BAZ to BAZNAS; secondly to the community for transparency and to maintain community trust. Implications: This research is expected to contribute to the zakat management system at the mosque zakat collection unit, especially in the field of collecting zakat funds by working with related institutions